Pengembangan Media Pembelajaran E-Modul Berbasis PBL untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik: Development of PBL-Based E-Module Learning Media to Improve Students' Problem-Solving Skills - Nurhalimah Rahma Suci Marpaung; Katrina Samosir (ITScience (Information Technology and Science), 2025)
This research was conducted to develop a valid and practical PBL-based e-module learning media that can improve the mathematical problem-solving abilities of eighth-grade junior high school students in the context of the Pythagorean Theorem material. A pre-experimental method with a one-group pretest-posttest design was employed, and the ADDIE development model was adopted. The instruments in this study include: (1) Validation sheet, consisting of media validation with a percentage of 93.05%, material validation 91.26%, and test validation 89.62%. The validation results show that all instruments used are classified as very valid. (2) Practicality sheet, which is seen from the teacher response questionnaire with a percentage of 94.54% and student responses with a percentage of 83.63%. The results of the questionnaire state that the learning media developed are classified as very practical. (3) Problem-solving ability test, which is seen through the N-gain value based on the pretest and posttest results for an average value of 33.33 (pretest) and 80.20 (posttest), where 54% of students experienced an increase in ability in the high category and 46% of students experienced an increase in the medium category. The average N-gain score of 0.703, classified as high, indicates an increase in students' problem-solving ability after using the developed learning media.